The Effect of Interactive Learning Media Based on Mathplayground on the Learning Outcomes of the Students of Fraction Material Class IV SDN Kedung Dalem III - Vita Rahmatun Nazilah; Ribut prastiwi Sriwijayanti; Ludfi Arya Wardana (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to determine the effect of interactive learning media based on Math Playground on student learning outcomes on fraction materials in class IV SDN Kedung Dalem III. The problem studied is whether there is a significant influence between the use of interactive learning media based on Math Playground on student learning outcomes in grade IV SDN Kedung Dalem III. This study uses a quantitative method with a one group pretest-posttest design. The sample of this study were fourth grade students of SDN Kedung Dalem III, totaling 17 students. The research instrument used is a test (Pretest-Postest) of student learning outcomes on fraction material, which consists of 10 multiple choice questions. The results of the analysis using the wilcoxon test show that the sig value (2 tailed) is 0.000 which indicates significance <0.05 so that H0 is rejected and H1 is accepted. This shows that the interactive learning media Math Playground has a significant effect on improving student learning outcomes. The conclusion of this study is that Math Playground interactive learning media can improve student learning outcomes on fraction material. Therefore, teachers and educators can use Math Playground as an alternative learning media to improve student learning outcomes.